Challenges in the Diagnosis and Management of Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disease (MOGAD) - Lekha Pandit (Annals of Indian Academy of Neurology)
Myelin oligodendrocyte glycoprotein antibody-associated disease has been recently identified to be a distinct autoimmune central nervous system disorder. There is significant clinical and radiological overlap with multiple sclerosis and aquaporin-4-IgG–associated neuromyelitis optica spectrum disorders. Clinical course is variable in that patients may have a monophasic or relapsing course, disease severity is unpredictable, and unlike other idiopathic autoimmune inflammatory disorders, there is no gender predilection and it is more likely to affect pediatric population. There are no clear-cut treatment guidelines. Duration and dose of oral steroids after the first attack, role of immunosuppressants in relapsing disease, and duration of therapy for the latter are not certain. Currently, there are no disease-specific therapies available, though some novel therapies are under trial. Some of these challenges will be addressed in this paper.